Real-world study of direct oral anticoagulant dosing patterns in patients with atrial fibrillation - Gustafson WL; Saunders J; Vazquez SR; Jones AE; Witt DM (Centro de Investigaciones y Publicaciones Farmaceuticas, 2019)
Background: Direct oral anticoagulants (DOACs) are preferred for stroke prevention in atrial fibrillation (AF). However, off-label doses have been associated with increased risk of adverse events. Objective: The objective of this study was to compare the frequency and outcomes of labeled versus off-label DOAC dosing in patients with AF. Methods: This retrospective cohort study included adults diagnosed with nonvalvular AF (NVAF), discharged from University of Utah Health on DOAC therapy between 7/1/2017 and 9/30/2017. The primary outcome was off-label DOAC dosing frequency, defined as dosing inconsistent with manufacturer labeling. Secondary outcomes included variables associated with off-label dosing and a composite of adverse events (major bleeding, thromboembolism, and all-cause mortality) in the 90 days following the index hospital discharge. Results: Of 249 included patients, 16.1% were discharged with off-label dosing. Factors associated with off-label dosing included advanced age, lower body mass index, decreased renal function, use of rivaroxaban, and hepatic impairment. The majority of off-label patients (70%) received lower-than-recommended DOAC dosing. Prescriber rationale for off-label prescribing was documented in 25% of patients and included anti-Xa guided dosing, high risk for bleeding or thromboembolism, and prior history of on-therapy adverse events. The rate of adverse events between labeled and off-label DOAC doses was not statistically different (10.0% vs. 6.7%, p=0.299), although this is likely due to small sample size. Conclusions: Off-label DOAC prescribing for stroke prevention in NVAF at University of Utah Health was consistent or lower than previously published studies. Off-label dosing most often involved under-dosing of rivaroxaban. Future research should investigate the role of provider rationale and insight in optimizing DOAC therapy outcomes.